2016
DOI: 10.1177/0148607116658762
|View full text |Cite
|
Sign up to set email alerts
|

Severe Gut Microbiota Dysbiosis Is Associated With Poor Growth in Patients With Short Bowel Syndrome

Abstract: Patients with SBS, particularly those with suboptimal growth, have a marked gut dysbiosis characterized by a paucity of beneficial commensal anaerobes, resulting in a deficiency of key metabolic enzymes found in the gut microbiomes of healthy children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
88
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 32 publications
7
88
0
3
Order By: Relevance
“…Interestingly, we found that SBS III patients had a strikingly higher proportion of Lactobacillus in fecal microbiota and dominance of Lactobacillus was associated with shorter PN duration. Previous studies showed that Lactobacillus were enriched in SBS patients who had weaned off PN but depleted in SBS children with poor growth . Moreover, SBS III patients relatively have a quicker intestinal adaption and better clinical outcome.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, we found that SBS III patients had a strikingly higher proportion of Lactobacillus in fecal microbiota and dominance of Lactobacillus was associated with shorter PN duration. Previous studies showed that Lactobacillus were enriched in SBS patients who had weaned off PN but depleted in SBS children with poor growth . Moreover, SBS III patients relatively have a quicker intestinal adaption and better clinical outcome.…”
Section: Discussionmentioning
confidence: 98%
“…Commensal intestinal microbes are involved in fermentation and absorption of undigested carbohydrate, normal development of immune system, and promotion of intestinal mucosal growth and integrity . Several studies have shown that the disruption of intestinal microbiota leads to delayed enteral diet, prolonged PN dependence, poor growth, and predisposition to liver disease in pediatric SBS patients . Thus, determination of the changes in gut microbiota of SBS patients may point to new therapies that ameliorate abdominal symptoms and contribute to intestinal adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiome is important for several functions such as fermentation and absorption of nutrients in the colon, development of the immune system, and intestinal mucosal growth and integrity . There is growing evidence that certain groups of bacteria such as Clostridia are important for normal intestinal function and protection against intestinal diseases, whereas other proinflammatory bacteria, specifically certain species belonging to Enterobacteriaceae, are harmful …”
Section: Introductionmentioning
confidence: 99%
“…A majority of patients are diagnosed clinically with small bacterial overgrowth as an effect of dysbiosis. Treatment often requires multiple courses of antibiotics, further disrupting and altering their gut microbiome …”
Section: Discussionmentioning
confidence: 99%